Evaluation of Daytime Sleepiness and Academic Performance in Dentistry Students - Pierri, Ricardo Augusto Gonçalves; Oliveira, Marina Reis; Trento, Guilherme; Spin-Neto, Rubens; Rodrigues, Marcos Marques; Pereira-Filho, Valfrido Antonio (European Journal of General Dentistry, 2021)
Objective This study aimed to evaluate the daytime sleepiness and sleep quality of students in different academic years of the dental school program.Materials and Methods A total of 221 students, from the 1st to the 5th year, answered the questionnaires: Epworth, Pittsburg, Nasal Obstruction Symptom Evaluation, and Berlin, related to daytime sleepiness, sleep quality, nasal obstruction, and obstructive sleep apnea syndrome (OSAS), respectively.Statistical Analysis The Kolmogorov–Smirnov test was used to assess the normality of continuous quantitative data and, posteriorly, the chi-square test was used to show if there were any associations. The significance level adopted was 5%.Results An association between daytime sleepiness and nasal obstruction was observed at the beginning of the school year (T1) (p = 0.002) and at the end of the school year (T2) (p = 0.043). In T2, an association between nasal obstruction and sleep quality was also observed (p = 0.026). The academic performance (AP) was only associated with the OSAS in T1 (p = 0.012). There was no significant difference in AP between the beginning and the end of the academic year (p = 0.935).Conclusion With the methodology used, it was observed that nasal obstruction influenced sleep quality and daytime sleepiness, and daytime sleepiness did not have any influence on AP.
Keywords: daytime sleepiness; dentistry; nasal obstruction; sleep quality